EKSPLORASI PERAN PERCEIVED QUALITY DAN BRAND IMAGE TERHADAP REPURCHASE INTENTION PADA PRODUK KECAP BANGO - Dari, Seftia Triwulan; Santoso, Wahyu; Setiawan, Risqi Firdaus (Agriculture Faculty of Flores University, 2025)
Bango soy sauce is one of the popular brands that ranks first in the Top Brand Award, but has experienced a decline in the Top Brand Index value starting in 2021, indicating a decrease in consumer repurchase intention. This decline is related to the weakened perceived quality and brand image of Bango soy sauce. Thus, the purpose of this study was to investigate the impact of brand image and perceived quality on repurchase intention among Bango soy sauce product users in Surabaya City. Surabaya City was purposefully selected as the research location, with a focus on modern retail. A total sample size of 100 respondents was determined using the Cochran formula, and the accidental sampling method was used as the sampling technique. SmartPLS 4.0 software is used for data analysis using Partial Least Squares based on Structural Equation Modeling (PLS-SEM). The analysis's findings demonstrate that repurchase intention is positively and significantly influenced by perceived quality and brand image.